Social Commentary Influence In Printmaking Artworks Under Barjeel Art Foundation - Omar A., Badghaish Amal (2023)
Social commentary plays a crucial role in the field of art. In Western societies, this has been prevalent for a long time, with social commentary having a strong connection to printmaking. However, in Arab societies, social commentary art has not been as widely recognized or studied. Although there are artworks in Arab countries that carry powerful messages, it is unclear how social commentaries relate to Arab printmaking as kind of art. This study aims to explore social commentary influence in Arab printmaking artworks, with a specific focus on the collection of Barjeel Art Foundation